Clinical Impact of β-Lactamase–producing Enterobacteriaceae in Sputum of Cystic Fibrosis Patients. Issue 2 (February 2016) - Mussaffi, Huda; Shvalb, Naama Fisch; Ben-Zvi, Haim; Livni, Gilat; Mei-Zahav, Meir; Prais, Dario; Stafler, Patrick; Steuer, Guy; Blau, Hannah
Abstract : This case series describes 18 cystic fibrosis (CF) patients of a 135-patient CF center cohort with extended spectrum β-lactamase–producing Enterobacteriaceae, from 2003 to 2012. Four had chronic infection. Prevalence increased annually from 0 to 6.35%. Risk factors compared with the 2010 CF center cohort included continuous inhaled antibiotics ( P = 0.014) and courses of intravenous antibiotics during the year before first isolation ( P = 0.009). Hospitalization rates were 1.05/year and 0.47/year preinfection and postinfection, respectively ( P = 0.02). Slope of forced expiratory volume at 1 second% predicted remained unchanged during 12 months. Abstract : Supplemental Digital Content is available in the text.